BACTERIAL SPECTRUM AND SUSCEPTIBILITY PATTERNS OF PATHOGENS IN ADULT FEBRILE NEUTROPENIC PATIENTS: A COMPARISON BETWEEN TWO TIME PERIODS - Zahid, Khawaja Farhan; Hafeez, Haroon; Afzal, Ammarah (Journal of Ayub Medical College Abbottabad, 2009)
Background: The aim of this study was to study trends in bacterial spectrum and susceptibility patterns of pathogens in adult febrile neutropenic patients during two time periods. Methods: We retrospectively reviewed the medical records of 379 adult oncology patients admitted with chemotherapy induced febrile neutropenia at our institute during years 2003 and 2006. Results: A total of 151 organisms were isolated during the two calendar years. Gram negative bacteria accounted for 57.6% of organisms, while gram positive organisms accounted for 42.3% of the total isolates. The most common organisms were: Escherichia coli (23.1%), Staphylococcus epidermidis (13.9%), Pseudomonas aeruginosa (12.5%) and Staphylococcus aureus (7.9%). The number of gram positive isolates showed an increase from 35% in 2003 to 47.2% in 2006 (p=0.13). During each calendar year, Staphylococcus epidermidis and Staphylococcus aureus were 100% susceptible to vancomycin and 33% strains of Staphylococcus aureus were methicillin resistant. Escherichia coli and Pseudomonas aeruginosa strains were highly sensitive to piperacillin/tazobactam and amikacin during both time periods. Resistance of Pseudomonas aeruginosa strains to ciprofloxacin increased from 0% in 2003 to 50% in 2006 (p=0.03). Conclusions: Gram negative organisms are the predominant organisms in adult febrile neutropenic patients at our institute. Initial empirical therapy with piperacillin/tazobactam seems appropriate to cover most gram negative pathogens while vancomycin to be added for suspected gram positive infections. During the two calendar years resistance of Pseudomonas aeruginosa strains to ciprofloxacin has significantly increased. Keywords: Bacterial spectrum, Febrile neutropenic patients, Empirical therapy